Pengaruh Lingkungan Kerja dan Karakteristik Individu terhadap Kinerja Karyawan pada PT. Karya Indah Alam Sejahtera di Gresik - Dewi, Ayu Puspita (Implementasi Manajemen & Kewirausahaan, 2021)
The purpose of this study was to determine the effect of work environment, individual characteristics, on employee performance at PT. Karya Indah Alam Sejahtera in Gresik. The type of research used by researchers is explanatory research with a quantitative research approach. The population in this study were 523 people who were included in the internal employees of the company PT. Karya Indah Alam Sejahtera in Gresik and the samples in this study were 84 people. The results showed that the work environment and individual characteristics had an effect on employee performance. The work environment and individual characteristics simultaneously also have a significant and positive influence on employee performance.